Transgender adolescent and young adult suicide: A bioecological perspective. Issue 3 (18th November 2021) - Anderson, Avery M.; Ford, Jodi
Abstract: Suicide is a public health crisis disproportionately affecting transgender adolescents and young adults. There are gaps in research evaluating this phenomenon using a multilevel, life‐course approach. The following paper will provide an overview of the current models of suicide, critique their applicability to understanding suicide among transgender youth, and discuss how using a bioecological systems approach will help to advance our understanding of suicide among transgender youth. Transgender adolescents and young adults often face unique combinations of interpersonal and intrapersonal challenges that require managing a stark misalignment of social characters, expectations, and roles. These factors are imposed by the complex interactions and influences of the bioecological systems in which transgender adolescents and young adults are situated. Future research is needed to elucidate the characteristics of bioecological adversity faced by this vulnerable population. Identification of these relationships are likely to highlight effective targets for multilevel interventions aimed at preventing suicide.